The Dialectic of Qur’an and Science: Epistemological Analysis of Thematic Qur’an Interpretation Literature in the Field of Social Sciences of Humanities - Anwar Mujahidin (UIN Sunan Kalijaga Yogyakarta, 2018)
This paper aims to analyze the results of published research from Indonesian researchers who have the theme of the thematic interpretation of the Qur’an (mawdūi) in the field of humanities. The question is how is the relationship of the Qur’an as a holy book as well as the source of Islamic sciences integrated and interconnected with the social sciences of the humanities. This research is a qualitative library research with a critical approach. The theory used is the epistemology of science and the scientific revolution, so it can be found the relationship between the Qur’an and science which are reflected in the object of research and criticism is made to make the constructive pattern of the Quran interpretation according to the epistemological framework. The results of the study show that there are three patterns of relations between the Qur’an and science. First, the Qur’an is a source of knowledge, in which the Qur’an and theories in the social sciences of the humanities are identical and in line. Second. The Qur’an is a source of universal value. The verses of the Qur’an which relate to the field of study in the social-humanities contain universal axiological values contributing to the construction of the social sciences of the humanities. Third, the Qur’an has a different perspective on an object of science, thus it contributes to build a paradigm of science. Of the three patterns, the second and third patterns can be developed as a pattern of relations between the Qur’an and science. The Qur’an is a social science-humanities paradigm. The relationship between the Quran and the social sciences of the humanities is a dialectical paradigmatic relationship, namely the dialogue between text and context and context to text.[Paper ini bertujuan menganalisis hasil penelitian yang telah terpublikasi dari para peneliti Indonesia yang memiliki topic tafsir al-Quran tematik (mawdūi`) pada bidang Ilmu Sosial Humaniora. Pertanyaannya adalah bagaimana hubungan al-Quran sebagai kitab suci sekaligus sumber ilmu- ilmu keislaman berintegrasi dan berinterkoneksi dengan ilmu-ilmu sosial humaniora. Penelitian ini adalah jenis penelitian kualitatif kepustakaan dengan pendekatan kritis. Teori yang digunakan adalah epistemologi ilmu dan revolusi ilmu pengetahuan, sehingga dapat ditemukan pola-pola hubungan al-Quran dan sains yang tercermin dalam objek penelitian serta dilakukan kritik untuk membuat pola tafsir al-Quran yang konstruktif sesuai kerangka epistemologi. Hasil penelitian menunjukkan adanya tiga pola hubungan al-Quran dan sains. Pertama, al-Quran adalah sumber ilmu, di mana al-Quran dan teori-teori dalam ilmu sosial humaniora adalah identik dan sejalan.Kedua.Al-Quran adalah sumber nilai universal. Ayat-ayat al-Quran yang berhubungan dengan bidang kajian dalam ilmu sosial-humaniora mengandung nilai-nilai universal yang aksiologis berkontribusi terhadap konstruksi ilmu sosial humaniora. Ketiga, al-Quran memiliki cara pandang yang berbeda terhadap suatu objek sains, sehingga berkontribusi untuk membangun suatu paradigma ilmu. Dari ketiga pola tersebut, pola kedua dan ketiga dapat dikembangkan sebagai pola hubunganal-Quran dan sains. Al-Quran menjadi paradigma ilmu sosial-humaniora. Hubungan al-Quran dan ilmu-ilmu sosial humaniora adalah hubungan paradigmatik dialektik, yakni dialog antara teks ke konteks dan konteks ke teks.]